Mechanical Characterization of Nano-SiO₂-Reinforced Epoxy Sandwich Composites With 3D Rayon Graphite Felt Core and Woven Carbon Fiber Face Sheets - Zahraa Jalood Nayyef; Nabil Kadhim Taieh; Ammar A. Beddai; Ying Li; Xi Liu; Adil Elrayah (Journal of Nanotechnology)
New epoxy (EP)-based sandwich composites have enhanced mechanical performance and optimized cost-effectiveness, as a result of composites’ increasing popularity. This study aims to develop composites with 3, 5, and 7 layers of woven carbon fibers (WCFs) layered on 3D rayon-based graphite felt (3D RGF) as the core of the sandwich composites. Using WCFs as face sheet layers increases flexural strength and modulus. Flexural strength increases to 226.92 MPa, and modulus increases to 15.18 GPa with 3 WCFs layers. Five layers increase modulus to 25.43 GPa and flexural strength to 370.21 MPa. Seven layers provide the highest modulus of 31.38 GPa and flexural strength of 405.07 MPa. Diverse concentrations of nanosilica (0.01, 0.1, 0.5, and 0.8 wt%) were embedded within the core to bolster its mechanical properties. Using an in situ casting method, an EP resin solution was infused into the structure, forming a bicontinuous composite. This method significantly enhances the toughness and adhesion between the fibers and the EP resin, resulting in superior mechanical properties. EP alone has 57-MPa tensile strength, but three layers of WCFs increase it to 531.38 MPa, five layers increase it to 647.24 MPa, and seven layers increase it to 764.40 MPa. The minimum tensile modulus of EP is 2.75 ± 0.5 GPa. The modulus increases significantly when layers of WCFs are added, reaching 9.75 GPa with three layers, 14.96 GPa with five layers, and a maximum value of 23.44 GPa with seven layers. When a little amount of nanosilica was added, the flexural properties of composites were significantly affected. Among all concentrations, 0. 5 wt% nano-SiO2 yielded the highest enhancement of flexural strength and modulus. At 0.1 wt% nanosilica, the flexural strength and modulus of the sandwich composites increase to 493.5 MPa and 30.5 GPa (23.4% and 24.5%). The peak occurs at 0.5 wt%, reaching 645.7 MPa and 41.5 GPa (61.4% and 69.4%). However, at 0.8 wt%, values drop to 560.1 MPa and 30.4 GPa, still showing 40.0% and 24.1% improvements. This study provides a new solution for reinforcing the mechanical properties of EP sandwich composites. Increasing the performance with nanofiller concentrations is also emphasized.